2017
DOI: 10.3390/ijerph14101271
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Relationship between Socio-Economic Status, Physical Activity and Sedentary Behaviour, and Adiposity in Young Adult South African Women Using Structural Equation Modelling

Abstract: Socio-economic status (SES) is an important predictor of obesity, but how it is associated with differences in physical activity and sedentary behaviour is less clear. This cross-sectional study examined the association between SES (sum of household assets), physical activity and sedentary time, and how they predict adiposity. Socio-demographic, anthropometric, and physical activity data on rural (n = 509) and urban (n = 510) South African women (18–23 years) were collected. Overweight and obesity prevalence, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
33
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 42 publications
6
33
1
3
Order By: Relevance
“…These findings are supported by a study from Soweto that found a direct association of SES with obesity among rural adult women, but found that among urban women the relationship was mediated by PI [16]. Another study from an urban African township in Cape Town, South Africa, showed that a high SES was associated with obesity in women but not in men [55].…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations
“…These findings are supported by a study from Soweto that found a direct association of SES with obesity among rural adult women, but found that among urban women the relationship was mediated by PI [16]. Another study from an urban African township in Cape Town, South Africa, showed that a high SES was associated with obesity in women but not in men [55].…”
Section: Discussionmentioning
confidence: 62%
“…Furthermore, work and domestic PA were not associated with obesity [39], supporting present findings. The commonly held position that increased physical activity is associated with a decrease in BMI [40,41] is in contrast with studies reporting positive associations between PA and BMI [15,16,42,43]. There is compelling evidence suggesting that PA has no influence of the risk of becoming overweight or obese [14], however, the value of PA on the general state of health is universally accepted [44,45].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Secondly, more than 78% of our participants had college or university education. Studies investigating the general population have shown that higher education levels reflect more favorable lifestyle habits, including participation in regular exercise . Still, a high proportion of our fitness club members (nearly 60%) reported low exercise frequency (<one time a week, or no exercise the last month).…”
Section: Discussionmentioning
confidence: 86%